Lockdown dilemma: ingestion of magnetic beads presenting as right iliac fossa pain and subacute small bowel obstruction. Issue 11 (4th November 2020) - Oyewole, Bankole; Sandhya, Anu; Maheswaran, Ian; Campbell-Smith, Timothy
Abstract : A 13-year-old girl presented with a 3-day history of migratory right iliac fossa pain. Observations and inflammatory markers were normal, and an ultrasound scan was inconclusive. A provisional diagnosis of non-specific abdominal pain or early appendicitis was made, and she was discharged with safety netting advice. She presented again 6 days later with ongoing abdominal pain now associated with multiple episodes of vomiting; hence, the decision was made to proceed to diagnostic laparoscopy rather than a magnetic resonance scan for further assessment. Intraoperative findings revealed 200 mL of serous fluid in the pelvis, normal-looking appendix, dilated stomach and a tangle of small bowel loops. Blunt and careful dissection revealed fistulous tracts that magnetised the laparoscopic instruments. A minilaparotomy was performed with the extraction of 14 magnetic beads and the repair of nine enterotomies. This case highlights the importance of careful history taking in children presenting with acute abdominal pain of doubtful aetiology.